EVALUASI KETERLAKSANAAN KOSP (KURIKULUM OPERASIONAL SATUAN PENDIDIKAN) PADA PEMBELAJARAN SISWA KELAS 5 SD NEGERI POPONGAN KEC. BRINGIN MENGGUNAKAN MODEL CIPP - Devi; Krisma Widi Wardani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to evaluate the implementation of the Operational Curriculum of Educational Units (KOSP) in the learning of fifth-grade students at Popongan State Elementary School using the CIPP (Context, Input, Process, Product) evaluation model. The CIPP model is used to comprehensively assess the suitability of the context, the readiness of resources, the learning implementation process, and the final results of KOSP implementation. This study employs a quantitative approach using a survey method through instruments such as questionnaires, observations, and interviews. The research subjects consisted of the school principal, fifth-grade teachers, and fifth-grade students. The analysis results showed that the implementation of KOSP at Popongan State Elementary School was categorized as “very high” with a percentage score for the context aspect of 83% (school principal) and 100% (teachers), input aspect of 75% (school principal) and 79% (teachers), process aspect of 83% (school principal) and 86% (teachers), and product aspect of 75% (school principal) and 84% (combined responses from students and teachers). These results indicate that KOSP has been implemented optimally, although there are still some technical challenges that can be improved. This study is expected to serve as a reference for the development of policies and strategies to improve the quality of curriculum-based learning at the school level.